Los animales no deben actuar como la gente - Barrett, Judi.; Barrett, Ron. (Buenos Aires : Ediciones de la Flor, 1992)
Depicts the inconveniences animals would be burdened with if they behaved like people.
Keywords: Animals -- Juvenile humor; Animal behavior -- Pictorial works